A synergy value analysis of sustainable management projects: Illustrated by the example of the aesthetic medicine industry - Tyrone T. Lin; Hui-Tzu Yen; Shu-Yen Hsu (Journal of Risk and Financial Management, 2022)
This study aims to construct a mathematical model to determine the dimensions of an economic, social, and environmental project with the goal of sustainable management. By identifying the optimal weights, the synergy values for sustainable management can be maximized. Taking aesthetic medicine companies as examples, this study attempts to construct the index projects of the economic, social, and environmental dimensions of sustainable management in an uncertain environment. Linear relationships (a combination of fixed synergistic values and varying synergistic values) are used to calculate the import optimal weight under optimistic, normal, and pessimistic circumstances. This study helped companies to introduce triple bottom line (TBL) indices to plan their issues under sustainable management and development, thus, enabling the parent company to achieve the optimal weight for the project costs to put in its subsidiaries. Additionally, this study prioritizes the weight of the influence on the management of the aesthetic medicine industry according to the risk probabilities, to minimize the uncertainties of risk management in corporate management and reduce the possibility of direct and indirect cost losses caused by financial distress, functional fluctuations, and negative impact on the medical equipment market, thereby maximizing the estimated total project value under sustainable management. This study constructs an aesthetic medicine-specific mathematical model concept using the triple bottom line model as the basis for sustainable corporate management and proposes an approach to obtain sustainable weight in uncertain conditions. By doing so, companies can add various managerial methods for the same industry, and new ideas are provided to the academic community to discuss the development of decision-making assessment criteria for risk assessments in sustainable management.
Keywords: 650; sustainability; aesthetic medicine industry; functional training time; medical errors/dispute incidences; risk and financial management